Energetic interpenetrating polymer network (EIPN): enhanced thermo-mechanical properties of NCO-fMWCNTs/HTPB PU and alkyne-fMWCNTs/acyl-GAP based nanocomposite and its propellants. Issue 54 (18th May 2016) - Tanver, Abbas; Huang, Mu-Hua; Luo, Yunjun
Abstract : Novel energetic interpenetrating polymer network (EIPN) nanocomposite comprised of fMWCNTs covalently attached to HTPB and GAP by facile in situ polymerization technique. Abstract : A novel energetic interpenetrating polymer network (EIPN) nanocomposite was designed and tested, which was comprised of functionalized MWCNTs (fMWCNTs) covalently attached to hydroxyl terminated polybutadiene (HTPB) and glycidyl azide polymer (GAP) by a facile in situ polymerization technique. Three types of fMWCNTs (COOH-fMWCNTs, NCO-fMWCNTs and alkyne-fMWCNTs) were synthesized and well characterized by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, transmission electron microscopy (TEM), dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA). The effect of fMWCNTs on the mechanical, dispersion, and thermal properties of NCO-fMWCNTs/HTPB PU and alkyne-fMWCNTs/acyl-GAP click was investigated and synergetic properties were achieved as compared to neat HTPB and GAP PU networks. Here we develop for the first time an EIPN nanocomposite based on NCO-fMWCNTs/HTPB PU and alkyne-fMWCNTs/acyl-GAP with different weight ratios and superior tensile strength of 8.17 MPa with 312% elongation at break was achieved with thermally more stable crosslinked networks. A solid composite propellant based on NCO-fMWCNTs/HTPB PU and alkyne-fMWCNTs/acyl-GAP was also prepared and mechanical and thermal properties investigated. An extensive enhancement in the thermo-mechanical properties of the NCO-fMWCNTs/HTPB PU and alkyne-fMWCNTs/acyl-GAP EIPN based nanocomposite have been achieved which may be ascribed to good dispersion of fMWCNTs in the polymer matrix, strong interfacial bonding and entanglements of crosslinked networks during in situ polymerization. This EIPN based composite propellant with improved mechanical and thermal properties paves the way for its straightforward application as a solid fuel in advanced missile technology.